Appendix 5.17: Marcos Pays for Propaganda - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
For Every Tear A Victory helped win Marcos the 1965 elections. It is the foundational book on the Marcos mythology. Even today, at the Ferdinand E. Marcos Presidential Center museum in Batac, Ilocos Norte, the exhibits are arranged based on the book’s narrative. How much did it cost to make this crucial text? According to a public relations specialist hired by the Marcoses, Leonard Saffir, Marcos paid at least USD 15,000.00 (about PHP 58,500.00 in 1963) to the book’s author, Hartzell Spence, and guaranteed McGraw-Hill, the book’s publisher, a sale of the book worth USD 10,000.00. To understand how expensive this deal was, the annual salary in 1963 of the Philippine president was PHP 30,000.00 as per the 1935 Constitution (the controlling law on this matter until 1964).